PENDIDIKAN HUMANISME DALAM DALAM PERSFEKTIF PENDIDIKAN MUHAMMADIYAH - Lazuardi Lazuardi (FORUM PAEDAGOGIK, 2018)
This paper contains about humanist education in the perspective of Muhammadiyah education. The humanist education meant in this paper is Muhammadiyah's effort in providing space for students to develop their potential both physically and spiritually which is facilitated through Muhammadiyah educational practices. Conceptually the Humanistic idea was born from the exploration of the source of Islam, namely the Koran and the Sunnah as a source of Islamic education. Furthermore, this organization has systematized it as a humanistic education model. However, at the implementation level, this humanistic education has not received serious attention due to technical problems in the internal education of Muhammadiyah mass organizations.